Strengthening Students' Career Interest in STEM Fields through Career Seminars - Rabiudin; Darmawan, Andri; Widyastuti, Tiara (Al-Khidmah : Jurnal Pengabdian dan Pendampingan Masyarakat, 2024)
High school students' interest in careers in science and engineering tends to be low, especially in certain regions such as Papua. This can hinder human resource development and the development of the region. This activity aims to educate students to be able to pursue a career in science and technology. In addition, this activity is also intended to evaluate the effectiveness of a career seminar in increasing high school students' interest in working in science and engineering. The career seminar activity was carried out by presenting presentations from speakers accompanied by discussion sessions and interactions with participants. Surveys and interviews were used to collect data before and after the event to measure changes in student interest. This seminar succeeded in increasing student interest in studying and pursuing careers in science and engineering. The data showed a significant increase in students' understanding of career opportunities and their role in regional development. Because of its benefits, it is recommended that similar activities be carried out periodically and involve more parties, such as local industries and universities, to provide broader and deeper insights to students.